Single Working-class Women and the City in Java and Vietnam. Issue 1 (2nd January 2016) - Peters, Robbie
Abstract: Through investigation into the lives of single migrant women who work as department store salesgirls in Surabaya and Ho Chi Minh City, this paper suggests that while commonalities exist with regard to their controlled use of beauty in the workplace, their lack of time and disposable income, and the temporary nature of their right to live in their respective cities as migrants, there are significant differences between them. These differences run contrary to conventional stereotypes of the "outspoken" Javanese woman and the "servile" Vietnamese woman, which in turn are based on stereotypes of the bilateral Southeast Asian kinship tradition and the patrilineal East Asian kinship tradition respectively. Taking into account the forces for and against conservative gender relations in both societies, this paper suggests that it is the Vietnamese working-class woman who exercises more power over how she lives in the city.